HUBUNGAN PENGETAHUAN SIKAP DAN STIGMA MASYARAKAT TERHADAP PENYAKIT HEPATITIS B DAN PENCEGAHANNYA DI DESA WONODADI ASRI KABUPATEN OKU TIMUR - Fitriani Agustina; Toto Harto (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2021)
Hepatitis B is an infectious disease in the liver tissue caused by a virus that comes from the hepadnavirus family. Hepatitis B is divided into two, namely, acute hepatitis B and chronic hepatitis B. About 30% of chronic hepatitis B progresses to liver cancer, whether diagnosed by media practitioners or not. This case can attack all ages, races and sexes (Masriadi, 2014). This research was conducted in Wonodadi Asri Village, East OKU Regency. This research was conducted in January 2020. This research used a descriptive analytical method with a cross sectional approach. This study uses a questionnaire measuring tool. The samples in this study were 98 respondents. From the results of statistical tests carried out with the Chi-Square examiner, it was found that knowledge with value (p value = 0.000), attitude with value (p value = 0.022) and stigma with value (p value = 0.000) which means that there is a significant relationship between knowledge of people's attitudes and stigma against Hepatitis B and its prevention. Conclusion The results of this study are that there is a relationship between knowledge of attitudes and community stigma in Wonodadi Asri village, East Oku district in 2020 so it can be seen that people's attitudes and stigma depend not only on knowledge but on a sense of empathy for sufferers.